Label free characterization of soft tissue with optical polarization technique. (28th May 2020) - Yousaf, Muhammad Sajid; Khurshid, Ahmat; Ahmad, Iftikhar; Mahmood, Rashid; Alam, Masroor; Bukhari, Sarwat Batool; Khan, Junaid Ahmed; Rafi, Muhammad; Ikram, Masroor
Abstract: Polarized light assessment of biological samples is a simple, fast, non-invasive and efficient technique for tissue characterization. Herein, we explore the optical polarization signatures of ex vivo muscle tissue samples of chicken, ox/beef and goat (male)/mutton, through Mueller matrix spectro-polarimetry in the spectral range of 570–800 nm. The results showed statistically significant ( p < 0.01) differences in the depolarization and retardance among the tissue samples of three animal species. These findings demonstrate a novel application of optical polarimetry, namely the characterization of muscle tissues from different animal species, which may be extended for differentiating various sources and quality assessment of meat.